The Role of Modern Public Relations Strategies in Developing Communication Performance at Service Institutions in Algeria. - Miloud, Souli (Journal of Ecohumanism, 2026)
The present study explores the influence of modern public relations strategies on the communication effectiveness of service institutions. The focus is on the Algerian water and sanitation company SEAAL. The text goes on to address the manner in which these strategies enhance communication in the face of considerable challenges within the water sector. Utilising a goal-oriented methodology, the study discloses that SEAAL adroitly employs integrated communication strategies that prioritise transparency, social responsibility, and technology. The efficacy of these approaches in enhancing the company’s mental imagery is a subject that merits further investigation. However, despite SEAAL’s endeavours to enhance its public image, further development is required to achieve the intended outcomes. The research emphasises the interconnectedness of public relations strategies and communication performance, and it provides recommendations for future enhancements in the domain of mental imagery.